Models of Equity Valuation: The Great Serm Bubble: Discussion - Lerner, Eugene M. (Journal of Finance, 1970)
Eugene M. Lerner, Models of Equity Valuation: The Great Serm Bubble: Discussion, The Journal of Finance, Vol. 25, No. 2, Papers and Proceedings of the Twenty-Eighth Annual Meeting of the American Finance Association New York, N.Y. December, 28-30, 1969 (May, 1970), pp. 320-321